THE DYNAMICS OF MORAL EDUCATION IN THE FAMILY AND SCHOOL: SYNERGY OR CONFLICT OF VALUES AMIDST THE PLURALISM OF CONTEMPORARY INDONESIAN SOCIETY - Aslan Aslan; Miranu Triantoro (Indonesian Journal of Education (INJOE), 2026)
This study aims to analyse the dynamics of moral education within the family and school amidst the pluralism of contemporary Indonesian society, focusing on whether there is synergy or conflict of values in the character formation of students. It employs a literature review (library research) using a qualitative-descriptive approach. The findings indicate that the dynamics of moral education are dialectical: on the one hand, value synergy can be achieved when families and schools build authentic collaboration through open communication, shared role modelling, coordinated value instillation, and inclusive normative agreements that result in the consistent and profound internalisation of character in children. On the other hand, value conflicts remain a significant structural challenge, stemming from a clash of paradigms between the family’s religious-traditional values and the school’s secular-universal values, generational dissonance between parents and Generation Z, as well as the influence of moral relativism from social media and globalisation, which has the potential to trigger a moral identity crisis and deviant behaviour. This study concludes that pluralism can serve as social capital or a source of moral fragmentation, depending on the institutional and cultural capacity to bridge value differences through dialogue and transformation. Strategic recommendations include the reformulation of policies supporting tripartite collaboration (family-school-community), strengthening teachers’ capacity in multicultural education, and empowering parents as strategic partners in shaping the character of a Generation Z that is adaptive yet principled.